Left hemisphere dominance for processing vocalizations in adult, but not infant, rhesus monkeys: field experiments. - Hauser, M D (1994)
In humans, the left hemisphere of the brain is dominant for processing language. To assess the evolutionary origins of this neuropsychological mechanism, playback experiments were conducted on a large population of free-ranging rhesus monkeys (Macaca mulatta). Playbacks provided an equal opportunity to orient the right or left ear toward the speaker. Results revealed that 61 of 80 adult rhesus favored the right ear (left hemisphere) when vocalizations from their own repertoire were heard but favored the left ear when listening to heterospecific vocalizations. In contrast, infants less than a year old showed no perceptual asymmetry for conspecific or heterospecific calls. Thus, like humans, adult rhesus monkeys also evidence left hemisphere dominance for processing species-specific vocalizations. The emergence of such asymmetry, however, may depend on both differential maturation of the two hemispheres and experience with the species-typical vocal repertoire.